FACTORS THAT INFLUENCE COMMUNITY PARTICIPATION IN DEVELOPMENT PLANNING IN KASIHAN DISTRICT, BANTUL REGENCY, YOGYAKARTA - Ghina Nabilah Effendi (TheJournalish: Social and Government, 2020)
The research aims to look at the level of community participation or community power in development planning related to decision making for the common interest and welfare and to know the factors that influence the level of community participation in development planning for sustainable development programs. This research uses quantitative methods by collecting data through questionnaires and analyzed using SEM PLS Analysis. The results showed that the level of community participation in development planning through the Musrenbang in Kasihan Subdistrict, Bantul Regency, Yogyakarta Province was still not optimal and tended to below, and among several internal and external factors tested showed that the age, level of education, type of work, communication and leadership has a relationship with community participation. And the thing that shows the biggest factor influencing the level of community participation in the type of work that has a significant impact that influences the low level of community participation in Kasihan District because it is dominated by peasants and the private sector which then makes the tendency of ordinary people not want to participate in development planning in the District Kasihan, Bantul Regency, Yogyakarta Province.